Miskonsepsi Dalam Pembelajaran IPA - Kurniyatul Faizah (IAI Darussalam, 2016)
In general, students who learn from several lessons already have some preceding knowledge related to the lessons they learn to learn. This also happens to students who are processing to study science. The students already have some experience and knowledge related to nature. Whether knowledge is true or false in theory. Having prior knowledge, it creates intuition and